PENERAPAN MANAJEMEN RESIKO TERHADAP NILAI PERUSAHAAN - Hendratni, Tyahya Whisnu; Retnosari, Dewi (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- The purpose of this study is to analyze the influence of risk management implementation on the firm’s value in the banking industry which is listed on the Indonesian stock exchange in the period 2015- 2019. Design/methodology/approach- Risk management implementation is quantified by three models. In the First Model, financial ratios such as net interest margin to total assets (NETIM), non-interest margin to total assets (NONIM), provision for impairment loss to total assets (prov), and capital adequacy ratio (CAR) are used to quantify the risk management Variable. In the second model, we use the average (AVG) of all the ratios above. In the third model, we use the principal component analysis (PCA) value from all the ratios above to quantify the overall risk management implementation of the banks. Findings- The result shows that each model of risk management implementation has a different output. In the first model, NONIM has a significantly positive effect and CAR has a significantly negative effect on firms’ value on the banking industry. In the second model, the AVG value has a significantly positive effect on the firm’s value in the banking industry. Then the third model, PCA value, has a significant effect on the firm’s value.. Keywords: risk management, the banking industry